GROWTH PERFORMANCE OF MEAT PRODUCTION AND EXPORT IN PAKISTAN: AN - A. A. Randhawa; H. Magsi; A. H. Shah (Journal of Animal and Plant Sciences, 2018)
The study attempts to evaluate the growth performance of meat production from 1994-95 to 2016-17 as well as export during ( 1998-2017) in Pakistan. Annual meat production and export data were collected from secondary sources like; Economic Survey of Pakistan, Journals/year books published by Pakistan Bureau of Statistics as well as from research articles. Findings of the present research revealed considerable variations in meat type to type and year to year. The beef production exhibited negative growth in 1995-96. Mutton also shown negative growth rate in 1995-96 and 2005-06. Similarly, the result of poultry growth performance analysis indicated negative growth in 1997-98 while huge growth in sector is recorded during the following period up to year 2016-17. On the other hand, Pakistans meat exports exhibited negative growth during 2000-02 and 2016-17. Although, over the time the growth rates of meat production and export has been good. Based on findings of the present work, it is strongly recommended for the cautious policy interventions, particularly regarding training of all sectors involved in meat production and export to ensure the handsome share in global Halal meat market. generating revenue through the exports of live animals.
Keywords: Beef; Mutton; Poultry; Meat production; Meat export; Growth performance.